IDENTITY AND INFINITY: ALTERNATE MODES OF SCRIBING THE SELF: A COMPARISON OF MARIO VARGAS LLOSA’S AUNT JULIA AND THE SCRIPTWRITER AND YANN MARTEL’S LIFE OF PI - R, Govind (ShodhKosh: Journal of Visual and Performing Arts, 2024)
An active engagement with the notion of the ‘self’ in modes of confrontation, contestation and conjuration has been an important tropological concern of fictional narratives, especially of an autobiographical intent and tone. Any coherent and significant concept of the ‘self’ entails a conglomeration of conscious and subconscious indices of subjectivities, intellectual sensibility, emotional drives and epistemological orientations, all of which are ideally conducive to artistic or material creativity. And, in life as well as in literature, it inevitably determines the ways and the extent to which the individual is capable of transcending the ‘personal’ to connect with the ‘other’ in varying degrees of empathetic identification. Literature is a terrain where one can encounter, on the one hand, protagonists who cross the confines of their self and feel one with the whole cosmos, and on the other, those who fail miserably in transcending the anxieties and fears of the personal, and recede into self-imposed reticence and insularity. The former is usually seen undertaking a self-chosen or imposed journey in which their inner psychic resources are unearthed and are ultimately traced to the vast eternity of cosmic energies. The latter is representative of the tragic consequences of the ruthless encroachment of normative social forces upon the personal space and the resultant subjugation of the individual self. There is also an in-between category of individuals who can strike a fine balance between their self and the social mores, through an ironic process of competitive negotiation. They consolidate their selves through the calibrated transgressions they perform upon the rules and rigours of social institutions and ethics, only to be re-inducted after a brief interregnum of ostracized animation.